Pattern of Disorders in Neurology Outpatient Department: Experience from a Tertiary Care Hospital in Bangladesh - Chowdhury, Ahmed Hossian; Ghose, Swapon Kumar; Ahmed, Kazi Gias Uddin; Hasan, ATM Hasibul; Saha, Kanol; Sina, Hashmi; Arifuzzaman, Md; Alam, Iftikher; Wazib, Amit; Khatun, Maksuda; et al. (Journal of Dhaka Medical College, 2017)
Objective: To determine the pattern of neurologic disorder in the specialized neurology out patient at tertiary care level. Methods: This observational study was carried out in specialized neurology outpatient clinic of Dhaka Medical College Hospital from July 2015 to July 2016, which included 8892 patients. Data were collected through a predesigned questionnaire from the hospital database kept at the clinic. Result: A total of 8892 patients were seen in neurology OPD in one year. About one third of the patients presented at 21-30 years of age. There was a male dominance (53%) with a male to female ratio of 1.12:1. Most of the patients had hypertension (3201, 36%) followed by diabetes and ischemic heart disease (1956, 22%; 1423, 16%) as co-morbid condition. Majority had Headache (4090, 46%) followed by vertigo (1067, 12%); vomiting (711, 8%) and neck and/ back pain (702, 8%) as presenting symptom at onset. Majority of the patients (46%) were diagnosed as headache disorder (Tension type headache in 33.5%, Migraine 7.5% and mixed headache in 5%) followed by ischemic stroke (896, 10%); polyneuropathy (446, 5%); vestibular disorder (441, 5%); movement disorder (267, 3%) and anxiety/depression (254, 3%). About 15% (1346) patient were undiagnosed at initial visit. Conclusion: Neurological diseases are not uncommon even at middle aged patients. Headache, vertigo, neck/back pain are common presenting symptom. Headache disorders and stroke are the commonest neurologic diagnosis at OPD. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 53-57